The Relationship Between Knowledge, Attitude, and Vaginal Care Behavior and the Incidence of Vaginal Discharge Among Pregnant Women - Rahmah Dwiningsih; Irma Jayatmi; Rita Ayu Yolandia (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: One of the physiological changes that occurs in pregnant women is vaginal discharge. Vaginal discharge that occurs during pregnancy is a health problem that requires attention, because it can have an impact on reducing maternal morbidity and mortality. Knowledge, attitudes and behavior of vaginal care are factors that influence the occurrence of vaginal discharge in pregnant women. Purpose: To determine the knowledge, attitudes and behavior of vaginal care towards the occurrence of vaginal discharge in pregnant women. Method: This type of study is an observational analytic with a cross-sectional approach. The sample of this study was 72 people. The sampling technique was consecutive sampling with inclusion criteria, namely gestational age 4-36 weeks who experienced vaginal discharge, had no history of urogenital infection. Results: There is a significant relationship between knowledge and the occurrence of vaginal discharge in pregnant women (p = 0.000), attitudes with the occurrence of vaginal discharge in pregnant women (p = 0.000; OR = 3.328), and vaginal care behavior with the occurrence of vaginal discharge in pregnant women (p = 0.000; OR = 10.105). Conclusion: The level of knowledge, attitudes and behavior regarding vaginal care plays an important role in influencing the occurrence of vaginal discharge in pregnant women. Suggestion: Pregnant women should be more proactive in seeking information and increasing their knowledge about the importance of maintaining reproductive hygiene. Hospitals should improve their health promotion programs, particularly education on personal hygiene for pregnant women.